2020
DOI: 10.1002/aelm.202000616
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Schottky Barrier and Contact Resistance at Metal–WSe2 Interfaces by Polymeric Doping

Abstract: devices, which can accommodate various materials via stacking. With respect to future applications, WSe 2 exhibits strong potential to be used in field-effect transistors (FETs), photodetectors, light-emitting diodes, and solar cells. [5-9] The metal-semiconductor (MS) interface is a critical factor influencing the electronic performance of 2D WSe 2 devices in that it is strongly correlated to device polarity. [10] Thus, the Schottky barrier height (SBH) is also an important parameter of the MS interface. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Moreover, it is reported that the defects, unintentional doping and charge trap states are also induced during the direct metal deposition which causes FLP and degrades device performance. [12,[24][25][26] Our vdWs BC approach overcomes the FLP, and controls the polarity of the WSe 2 FETs by contact engineering. First, the transfer of a 2D material onto the pre-patterned electrode avoids the high-energy involved direct deposition process which leads to the generation of defects and residues in the crystal structure of 2D materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is reported that the defects, unintentional doping and charge trap states are also induced during the direct metal deposition which causes FLP and degrades device performance. [12,[24][25][26] Our vdWs BC approach overcomes the FLP, and controls the polarity of the WSe 2 FETs by contact engineering. First, the transfer of a 2D material onto the pre-patterned electrode avoids the high-energy involved direct deposition process which leads to the generation of defects and residues in the crystal structure of 2D materials.…”
Section: Resultsmentioning
confidence: 99%
“…The demonstration of p-type intrinsic WSe 2 is more challenging and seldomly realized because of the FLP induced from interface states. [24][25][26] Herein, we test Au (5.31 eV) as the bottom electrodes, from which the fabricated device exhibits clear ambipolar behavior with an on-state hole current of approximately 1 µA µm −1 . Meanwhile, we found that the device presents Schottky contact, judging from the non-linear output curves (see Figure 2h).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[75] Much lower contact resistance has also been reported for transistors with their channels doped using dopants such as chloride molecules, [76] gold chlorides, [77] and polyvinyl alcohols. [56] For instance, Yang et al have reported low contact resistances of 0.7 and 0.5 kΩ µm measured for chloride molecular-doped WS 2 and MoS 2 with nickel contact, respectively. [76] Here, an additional mechanism is responsible for the reduced contact resistance.…”
Section: Surface-charge-transfer-doped Tmdsmentioning
confidence: 99%
“…[11] Weaker FLP was experimentally observed in WSe 2 with a relatively high pinning factor of 0.38. [56] This can be ascribed to weaker interactions with contact metals that would normally lead to the n-type or electron-dominated ambipolar behavior. [19,29,57] A high pinning factor of 0.3-0.5 has been suggested for monolayer WS 2 based on DFT calculations.…”
Section: Unipolarity Of 2d Transistorsmentioning
confidence: 99%